Development of an Effective Cryopreservation Protocol for Blue Catfish Oogonia. (6th August 2021) - Abualreesh, Muyassar; Myers, Jaelen N.; Gurbatow, Jeremy; Johnson, Andrew; Xing, De; Wang, Jinhai; Li, Shangjia; Coogan, Michael; Vo, Khoi; El Husseini, Nour; Creamer, David; Dunham, Rex A.; et al.
Abstract: Long‐term storage of oogonia and germ‐line stem cells provides an alternative to the limitations associated with cryopreserving eggs of important fish species. These cell types are less vulnerable to the stresses of freezing. Cryopreservation has enormous potential for aquaculture advancement, but protocols must be developed for each species and cell type since its success hinges on various input factors. Blue Catfish Ictalurus furcatus were selected as the test species in this study because of the need to improve fry production of Blue Catfish ♂ × Channel Catfish I. punctatus ♀ hybrids, which can be facilitated by storing oogonia in gene banks. Our objective was to develop a freezing protocol for oogonia of this species. We tested different permeating and nonpermeating cryoprotectants, concentrations of these agents, and freezing rates. We proved that all three factors influenced postthaw recovery of oogonia. Of the permeating cryoprotectants, 1.0 M dimethyl sulfoxide resulted in the most live cells with the highest viability percentages, and adding 0.2 M lactose with 10% egg yolk further improved the results. There were also specific interactions in which the effects of concentration and freezing rate varied among the cryoprotectant treatments. The most effective freezing rate was −1.0°C/min, and cell viability was reduced at −2.5°C/min and −5.0°C/min. From these results, we propose adding 1.0 M dimethyl sulfoxide with 0.2 M lactose and 10% egg yolk to cryomedia and freezing it at a rate of −1.0°C/min. By developing a cryopreservation protocol for a commonly cultured catfish, this work may guide the development of protocols for other species of interest.